The handbook of scholarly writing and publishing - Rocco, Tonette S., 1954-; Hatcher, Timothy Gary, 1950- (Jossey-Bass, 2011)
"There is a need for a resource that focuses on writing for publication that discusses the components of a manuscript, types of manuscripts, and the submission process. This groundbreaking book fills that need and includes information on how to develop writing skills by offering guidance on becoming an excellent manuscript reviewer and outlining what makes a good review. It shows how to craft scholarly papers and other writing suitable for submission to academic journals. The book offers on developing a manuscript suitable for publication in scholarly journals including tips on follow through with editors, rejection, and rewrites and re-submittals"--Resumé vydavatele
Část textu tištěna napříč
Keywords: studentská odborná činnost; odborné písemné práce; vysokoškolské kvalifikační práce; seminární práce; tvůrčí psaní; student professional activities; professional papers; academic theses; seminar papers; creative writing; příručky; handbooks, manuals, etc